Ebullition Regulated by Pressure Variations in a Boreal Pit Lake - Zhao, Kai; Tedford, Edmund W.; Lawrence, Gregory A. (Frontiers in Earth Science, 2022)
Methane ebullition from lakes is an important contributor to atmospheric greenhouse gases. However, ebullition is typically sampled at intervals greater than the duration of ebullition events, limiting our understanding of the factors controlling this flux. Here, we present high-frequency ebullition data from a single site in a boreal pit lake during the open-water season between June 24 and 21 October 2018. We record ebullition every 30 min for the first 2 months, and then every minute for the next 2 months. During the 4-month period, 24 ebullition events were recorded. These events generally lasted 2–4 days in response to low atmospheric pressure systems. The peaks in ebullition corresponded to troughs in atmospheric pressure. We provide empirical equations that incorporate a pressure threshold to model the time-series of ebullition events. Minor and gradual variations in mud temperature had no apparent effect on the observed ebullition events.